CatBoost Optimization Using Recursive Feature Elimination - Hadianto, Agus; Utomo, Wiranto Herry (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2024)
CatBoost is a powerful machine learning algorithm capable of classification and regression application. There are many studies focusing on its application but are still lacking on how to enhance its performance, especially when using RFE as a feature selection. This study examines the CatBoost optimization for regression tasks by using Recursive Feature Elimination (RFE) for feature selection in combination with several regression algorithm. Furthermore, an Isolation Forest algorithm is employed at preprocessing to identify and eliminate outliers from the dataset. The experiment is conducted by comparing the CatBoost regression model's performances with and without the use of RFE feature selection. The outcomes of the experiments indicate that CatBoost with RFE, which selects features using Random Forests, performs better than the baseline model without feature selection. CatBoost-RFE outperformed the baseline with notable gains of over 48.6% in training time, 8.2% in RMSE score, and 1.3% in R2 score. Furthermore, compared to AdaBoost, Gradient Boosting, XGBoost, and artificial neural networks (ANN), it demonstrated better prediction accuracy. The CatBoost improvement has a substantial implication for predicting the exhaust temperature in a coal-fired power plant.